1970
DOI: 10.3329/dujps.v9i2.7894
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Status in Vitiligo Patients

Abstract: ABSTRACT:Vitiligo is a common pigmentary disorder characterized by depigmented patches or macules caused by the destruction of melanocytes. The pathogenetic mechanisms involved in vitiligo have not been completely clarified. Oxidative stress and reduced circulating antioxidants could be important phenomena in the pathophysiology of vitiligo. We measured serum malondialdehyde (MDA) as an indicator of oxidative stress and serum zinc and vitamin C to check antioxidant status in thirty Vitiligo patients. Thirty he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Markers of lipid peroxidation are therefore considered as good measures of oxidative stress . Seventeen different studies including 745 patients clearly demonstrate increased MDA concentrations in patients with vitiligo . Five additional studies (2119 patients) confirmed increased lipid peroxidation in erythrocytes of patients with vitiligo …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of lipid peroxidation are therefore considered as good measures of oxidative stress . Seventeen different studies including 745 patients clearly demonstrate increased MDA concentrations in patients with vitiligo . Five additional studies (2119 patients) confirmed increased lipid peroxidation in erythrocytes of patients with vitiligo …”
Section: Resultsmentioning
confidence: 99%
“…14 Seventeen different studies including 745 patients clearly demonstrate increased MDA concentrations in patients with vitiligo. 7,[11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27] Five additional studies (2119 patients) confirmed increased lipid peroxidation in erythrocytes of patients with vitiligo. 13,[28][29][30][31] Hydrogen peroxide (H 2 O 2 ) and ROS.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Zn and Cu are involved in many homeostatic mechanisms of the body, such as specific immunity, inflammation and oxidative stress (OS) (10) . Decreased serum Zn and Cu levels have been reported in vitiligo by some investigators (11) , while others contradicted these findings (11) . Aim of study: this study aimed to detect the possible changes in the metabolism of serum Zn and Cu levels in vitiligo patients and their relation to the etiopathogenesis of vitiligo.…”
Section: Introductionmentioning
confidence: 96%
“…A number of physicochemical methods of analysis were used, such as thermal analysis [1][2][3], X-ray analysis [4] and different spectroscopic techniques [7][8][9][10]. The mode of chelation in these compounds has been discussed [ 1,2]. Spectrophotometric determination of uranium in its ores on the basis of these studies has also been performed [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…oxines and other phenolic compounds, have been reported previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A number of physicochemical methods of analysis were used, such as thermal analysis [1][2][3], X-ray analysis [4] and different spectroscopic techniques [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%